A Network Pharmacology Study on the Effects of Ma Xing Shi Gan Decoction on Influenza - Long Xi; Liu Le-Ping; Xu Xin-Yi; L.I. Ling; Zhang Guo-Min (KeAi Communications Co., Ltd., 2020)
Objective: Pharmacological methods were used to screen targets and signaling pathways of Ma Xing Shi Gan Decoction (MXSGD) during influenza treatments, and mechanisms underlying anti-influenza effects were elucidated. Methods: The Traditional Chinese Medicine Systems Pharmacology Database and Analysis Platform (TCMSP) and relevant literature were searched under predefined conditions to identify the main compounds and their targets. Interactions between the target proteins were predicted using the STRING database. Gene Ontology (GO) functional enrichment analyses and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed on the core targets involved in the influenza protein-protein interaction (PPI) network, using WebGestalt and the reactome database. iGEMDOCK was used for molecular docking of receptors and ligands to produce docking scores, and the results were visualized using Autodock and PyMOL. Results: In total, 126 major compounds and their respective targets were screened. 355 influenza target proteins and 1 221 influenza protein interactions were predicted using the STRING database. Influenza-related signaling pathways were strongly enriched in pharmacodynamic targets of MXSGD such as cytokine signaling in immune system and signaling by inter-leukin. The main biological process was response to the stimulates. Molecular docking results showed that RELA-Licochalcone A docking elicited by MXSGD, was superior to that of other target proteins and active compounds, suggesting that the docking site is also the main effector site of MXSGD during influenza treatments. Conclusions The results showed that MXSGD exerts anti-influenza effects by interfering with virus adsorption, inhibiting virus proliferation, influencing immune functions and protecting host cells, which may prevent inflammation-induced tissue damage.